The Equilibrium Spread Between Variable Rates and Fixed Rates on Long-Term Financing Instruments - von Furstenberg, George M. (Journal of Financial and Quantitative Analysis, 1973)
One of the most important innovations in bond financing and in mortgage lending has been the rapid adoption of variable-rate instruments in recent years. Notes and bonds bearing an interest rate between one and two percentage points above the prime rate are becoming common in corporate financing. Similarly, variable-rate mortgages (VRM's) with the interest rate tied to the deposit rate of S&L's or linked to the changing yields on competing investments have spread beyond Florida and California to many states. The Federal Home Loan Bank Board has recently endorsed the variable-rate concept and the Federal Home Loan Mortgage Corporation is preparing guidelines for secondary market operations in VRM's. Portfolio managers are thus taking note of the possibility of acquiring long-term instruments providing some of the resiliency of yields and a measure of real value protection characteristic of short-term issues.